MicroRNA binding site variants–new potential markers of primary osteoporosis in men and women - Yalaev, Bulat; Deev, Roman; Tyurin, Anton; Salakhov, Ramil; Smirnov, Kirill; Eremkina, Anna; Mokrysheva, Natalia; Minniakhmetov, Ildar; Khusainova, Rita (Frontiers in Genetics, 2024)
Introduction The identification of significant DNA markers of primary osteoporosis may gain new insights by studying genome regions involved in mechanisms of epigenetic regulation through interactions with microRNAs. Methods The authors searched for associations of polymorphic variants of microRNA binding sites of mRNA target genes and polymorphic loci of microRNA genes with primary osteoporosis in a cohort of women and men from the Volga-Ural region of Russia (N = 1.177). Results Using case-control association analysis, the authors found that rs1061947 (COL1A1), rs10793442 (ZNF239), rs6854081 (FGF2), and rs11614913 (miR-196a) were associated with osteoporotic fractures; rs5854 (MMP1) and rs2910164 (miR-146a) were associated with low bone mineral density; and rs10098470 (TPD52), rs11540149 (VDR), rs1042673 (SOX9), rs1054204 (SPARC), and rs1712 (FBXO5) were markers of both fractures and low bone mineral density. Among the identified associations, ethno specific trends were found, as well as sex-specific associations. Prognostic models were developed, among which the model for predicting osteoporosis in general in women (Area Under Curve = 0.909) achieved the highest level of predictive value. Thus, the potential role of polymorphic variants of microRNA binding sites in the development of primary osteoporosis in men and women from the Volga-Ural region of Russia was demonstrated.